Effect of Fins Arrangement on Thermal Performance in Microelectronics Devices - M Ekpu (Journal of Applied Sciences and Environmental Management, 2019)
Heat sink fins arrangement are important in heat management in microelectronics devices because it helps in the dissipation of heat from the chip level device to the environment and provide an efficiently working device. In this light, investigation was conducted on the effect of fins arrangement on thermal performance in microelectronics devices using the ANSYS finite element design software. The results obtained showed a maximum temperature range of between 95.27 – 126.79 oC, thermal resistance of 1.2 – 1.8 K/W, and thermal efficiency of 15 – 37%. The results demonstrated that, the arrangement of heat sink fins largely affects the thermal resistances and efficiencies of the microelectronic device. In addition, the A1 rectangular fins arrangement exhibited better thermal capabilities over the other fins arrangements investigated. This research can aid the development of future heat sinks to accommodate customer demands.